2018
DOI: 10.3766/jaaa.15098
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Processing Performance of the Middle-Aged and Elderly: Auditory or Cognitive Decline?

Abstract: Background: Despite the well-established relationship between aging and auditory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 52 publications
1
19
0
8
Order By: Relevance
“…At the same time, top-down processing that affects central auditory performance includes cognitive abilities, such as processing speed, attention, executive function, and memory. 20 Along with a decrease in the audibility of everyday speech, sensorineural hearing loss results in a distortion of the speech signal that often makes speech unclear even after appropriate amplification. This finding is supported by reports from older adults who, despite having clinically normal auditory thresholds, perform poorly on tasks of understanding speech in noisy backgrounds.…”
Section: Age-related Hearing Lossmentioning
confidence: 99%
“…At the same time, top-down processing that affects central auditory performance includes cognitive abilities, such as processing speed, attention, executive function, and memory. 20 Along with a decrease in the audibility of everyday speech, sensorineural hearing loss results in a distortion of the speech signal that often makes speech unclear even after appropriate amplification. This finding is supported by reports from older adults who, despite having clinically normal auditory thresholds, perform poorly on tasks of understanding speech in noisy backgrounds.…”
Section: Age-related Hearing Lossmentioning
confidence: 99%
“…Nevertheless, most studies about sensory processing and modulation in the elderly focus on sensory acuity or sensory impairment in a speci c sensory modality, mainly visual, auditory and vestibular [7][8][9][10][11], as measured in laboratory settings. Less is known about the ability of elderly people to process and modulate sensory information from various modalities, in daily life scenarios [5].…”
Section: Introductionmentioning
confidence: 99%
“…16 In particular, aging adults experience difficulty with speech perception (particularly speech-in-noise) and discrimination. 17,18 In a sample of 2015 adults aged 55 years and older, Golding 19 concluded that the detection of CAP abnormality for average older adults increased with age (binaural abnormality was detected in 27.3% of participants aged 64 years and lower; 44.3% of participant aged 65–74 years and 69.0% of participants aged 75 years and above), with men more likely to have a higher number of abnormal CAP test outcomes than women. The probability of demonstrating CAP abnormality increased with accompanying cognitive decline or increased hearing impairment.…”
Section: Introductionmentioning
confidence: 99%